A quick guide to API 510 certified pressure vessel inspector syllabus : example questions and worked answers - Matthews, Clifford (Quick guide (Cambridge, England), 2010)
The API Individual Certification Programs (ICPs) are well established worldwide in the oil, gas, and petroleum industries. This Quick Guide is unique in providing simple, accessible and well-structured guidance for anyone studying the API 510 Certified Pressure Vessel Inspector syllabus by summarizing and helping them through the syllabus and providing multiple example questions and worked answers. Technical standards are referenced from the API 'body of knowledge' for the examination, i.e. API 510 Pressure vessel inspection, alteration, rerating; API 572 Pressure vessel inspection; API RP 571 Damage mechanisms; API RP 577 Welding; ASMEVIII Vessel design; ASMEV NDE; and ASME IX Welding qualifications. Provides simple, accessible and well-structured guidance for anyone studying the API 510 Certified Pressure Vessel Inspector syllabusSummarizes the syllabus and provides the user with multiple example questions and worked answersTechnical standards are referenced from the API 'body of knowledge' for the examination.